I need 4 more tryna go to sleep rn :/
![I need 4 more tryna go to sleep rn class=](https://us-static.z-dn.net/files/d81/ee58db5f5b0881f282b898d7fe690a1e.png)
Answer:
Hello!!! Princess Sakura here ^^
Step-by-step explanation:
It is [tex]y=2x+2[/tex] because you should use [tex]m=\frac{y_{2}-y_{1} }{x_{2}-x_{1} }[/tex] then just plug it in using
(1, 4) and (-2, -2).
[tex]\frac{4--2}{1--2} =\frac{6}{3} =2[/tex]
That eliminates everything except the second one and the third.
So now we would find the b in the equation [tex]y=mx+b[/tex]
[tex]y=mx+b\\4=2(1)+b\\4=2+b\\2=b\\b=2[/tex]
and that's all